ChemInform Abstract: Unexpected Formation of N‐(1‐(2‐Aryl‐hydrazono)isoindolin‐2‐yl)benzamides and Their Conversion into 1, 2‐(Bis‐1, 3, 4‐oxadiazol‐2‐yl)benzenes. Issue 30 (4th July 2013) - Paraschivescu, Codruta C.; Matache, Mihaela; Dobrota, Cristian; Nicolescu, Alina; Maxim, Catalin; Deleanu, Calin; Farcasanu, Ileana C.; Hadade, Niculina D.
Abstract Isoindolinyl benzamides (III) are obtained as major products along with trace amounts of the predictable 1, 2‐bis‐aroylhydrazones.